How system level curriculum reform in English language teaching is enacted in a Chinese university - Yu, Aiqin (2016)
This research study examined College English teachers’ perceptions and enactment of a systemic curriculum reform at the classroom level in a Chinese university and the major issues involved in the complex process through an approach of case study. Drawing upon data collected through analysis of documents, semi-structured interviews and classroom observations, the study found that the enactment of China’s systemic College English Curriculum Reform was not a matter of simple implementation but the result of a more complex process which changed the original reform intention. The research, therefore, argues that multi-level challenges intertwined to shape teachers’ individualized classroom instructions. On the one hand, many factors worked together to facilitate teachers’ positive attitudes towards and adherence to the intended changes, such as the direction of national curriculum reform, harmonious workplace culture, teachers’ constructivist beliefs and self-reflection, and students’ feedback. On the other hand, levels of contextual tensions and gaps caused confusions and challenges in the teachers’ actual classroom instructions, such as the inconsistency among the policy strands, gaps between the institutional regulations and the national policy intent, classroom realities, Chinese students’ characteristics and teachers’ English proficiency. Thus, despite teachers’ general endorsement of and positive attitudes towards the proposed changes, they failed to enact them effectively and purposely at the grassroots level. All the teachers in this study experienced some changes in their teaching behaviors, but most of the changes were incremental and context-driven rather than radical and curriculum-oriented as intended.